#TITLE_ALTERNATIVE# - MITRA BARUNA (NIM 23606008), DIGIT
Design and build of a Hoverwing radio control model with specific requirements is conducted in this thesis to be used as a test model for observing transition phase on Hoverwing craft. The Hoverwing craft is a combination of a hovercraft and WiSE-craft. On Hoverwing, transition or transfer phase occurs from hover utilizing air cushion lift to pure airborne flight due to wing's aerodynamics lift. There is difference in basic concept between air cushion and aerodynamics lift, which emerging question about phenomena of flying in transition phase of a Hoverwing. To observe the phenomena on transition phase of a Hoverwing, a required test model is prepared. It was built for design requirement and objectives of span less than 1.5 m; using 2 separated propulsion system to produce thrust and (air cushion) lift to simplify execution on transition phase study; easy-to-built and lightweight model; as lowest speed as possible to support in observation; and as close possible with boundary to experience surface effect. Methodology of this thesis is conducting design and build of a Hoverwing model without a preface in analytical study of Hoverwing transition phase. Due to rarely found literature study in Hoverwing transition phase, it is apprehensive about inadequate result if an analytical study is priory performed. The Hoverwing model is build with minimum configuration and considering aspects which required for observation in transition phase. Those are the utilization of two variable controls for propulsion system to produce thrust and air cushion lift. When the observation of transition phase is conducted, a variation between increment in thrust to generate aerodynamics lift and decrement in air cushion lift is executed to simulate the condition of transition phase definition. The observation is conducted on flat surface of the ground and closed room to minimize wind disturbance. The XHW-1 Hoverwing model has been through a design and build process with technical data among others are: wing span 1.2 m; weight 0.755 kg; cruise speed 5.4 m/s for af = 4o ; 6,45 m/s for af = 0o ; and 7,9 m/s for af = -4o; wing to surface clearance 2.6 cm.